Wiley Encyclopedia of Operations Research and Management Science 2011
DOI: 10.1002/9780470400531.eorms0249
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Models Of Decision Making

Abstract: How should people decide in situations involving risk, time, uncertainty, and multiattribute alternatives? How do people actually decide? In this article, we contrast the rational decision maker with the modal subject observed in experiments and surveys. We use a simple setup to present preference models and decision processes that are descriptively more accurate than the rational model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…This was done to show the technical and scholastic ways on how to utilize pieces of evidence idiosyncratically drawn from educational dataset to inform and improve the teaching quality and performances for the stakeholders (teachers and students). The model (EPDM + ML) was developed through the amalgamation of the Text mining and Machine learning technique we grounded on the descriptive decision theory (Baucells & Katsikopoulos, 2011 ; Chandler, 2017 ) which studies the rationale behind the decisions that users (e.g., students) are disposed to make by means of the textual data quantification and statistical analysis. Studies that have looked into the text mining (e.g., sentiment analysis) method and its main application within the different studied contexts, have shown that machine learning techniques can be a good predictor of the students’ feedback and/or recommendation of the teachers’ performances or outcomes (Abu Zohair, 2019 ; Altrabsheh et al, 2014 ; De Fortuny et al, 2013 ; Dey et al, 2016 ; Litman & Forbes-Riley, 2004 ; Ofli et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This was done to show the technical and scholastic ways on how to utilize pieces of evidence idiosyncratically drawn from educational dataset to inform and improve the teaching quality and performances for the stakeholders (teachers and students). The model (EPDM + ML) was developed through the amalgamation of the Text mining and Machine learning technique we grounded on the descriptive decision theory (Baucells & Katsikopoulos, 2011 ; Chandler, 2017 ) which studies the rationale behind the decisions that users (e.g., students) are disposed to make by means of the textual data quantification and statistical analysis. Studies that have looked into the text mining (e.g., sentiment analysis) method and its main application within the different studied contexts, have shown that machine learning techniques can be a good predictor of the students’ feedback and/or recommendation of the teachers’ performances or outcomes (Abu Zohair, 2019 ; Altrabsheh et al, 2014 ; De Fortuny et al, 2013 ; Dey et al, 2016 ; Litman & Forbes-Riley, 2004 ; Ofli et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The outcome of their approach was a teaching outcome model (TOM) that showed to be useful not only for understanding the state-of-the-art methods or educational technologies related to teaching analytics and its implications for the future of education, prospects or mechanism in higher educational settings, but also in understanding the connection between the conceptual frameworks of teaching analytics (TA) (Ndukwe & Daniel, 2020 ), Learning Analytics (LA) (Ferguson, 2012 ; Herodotou, et al, 2019a , b ; Jones, 2019 ; Papamitsiou & Economides, 2014 ; Renz & Hilbig, 2020 ; Romero & Ventura, 2020 ), and learning design (LD) (Holmes et al, 2019 ; Mangaroska & Giannakos, 2019 ) in general. Accordingly, this study proposes the Educational Process and Data Mining plus Machine Learning model (EPDM + ML) that is built on conceptual frameworks of the TA, LA, and LD that is based on descriptive decision theory (Baucells & Katsikopoulos, 2011 ; Chandler, 2017 ) to provide a data-focused or analytical method that shows to be useful not only towards understanding of the teachers-students learning processes/outcomes to help inform and improve the quality of teaching pedagogies, but also the need for creating teaching-data-literacy or contextual-based analysis to uncover and address the different teaching–learning challenges that can be found within the higher education settings. The method (EPDM + ML) is described in detail in the next section of this paper.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, the study applied a two-step (mixed) methodology grounded on synthesis of the Data-structure approach [49] and the Descriptive decision theory [50], [51] to study the rationale behind the decisions that the learners are disposed to make by means of the textual data quantification (qualitative approach) and statistical analysis (quantitative approach). This was done using the students' evaluation of teaching (SET) dataset collected in a higher education setting.…”
Section: A the Rationale Of The Studymentioning
confidence: 99%